The Contribution of Western Humanism Ideas Towards Education Policy in The Dutch East Indies (1817-1942) - Surya, Riza Afita; Fikriya, Rif'atul (Paramita: Historical Studies Journal, 2022)
Abstract: This study aims to investigate the contribution of Western humanism ideas towards education policy in the Netherland Indies or Dutch East Indies. This study engaged historical method with four stages, namely heuristic, criticism, interpretation, and historiography. Humanism ideas that initially appeared in Italy obtained significant impact on European history afterwards. Thinkers as Rousseau, Montesquieu, Hobbes, and so on brought humanitarian ideas towards children, education as well as policy towards colonies as the result of humanisms movement. Those ideas clarify how children should be perceived and be treated that spread almost in many countries of Europe. At the time, many Europeans colonized several countries in Asia and Africa. Therefore, the ideas of humanism also encouraged the changes of colonial policy regarding how they should treat colonies in the sense of humanitarian thoughts. As many Southeast Asian countries were controlled by the western, Indonesia experienced several occupations of Europeans after initially colonized by the Portuguese, followed by Dutch, France and British. Officially, Indonesia under the realm of Dutch government since 1817 experienced the changes and shifts upon colonial treatment. After the collapse of VOC, Dutch colonial policy was affected by humanism movement. In term of education, there were policies being established such as Nativism, Concordantie, and Ethical Politic. Abstrak: Penelitian ini bertujuan untuk mengidentifikasi pengaruh gagasan humanisme Barat terhadap kebijakan politik di Hindia Belanda. Penelitian ini menggunakan metode sejarah yang terdiri atas, heuristik, kritik, interpretasi, dan historiografi. Gagasan humanisme pertama kali muncul di Italia memberikan dampak signifikan terhadap sejarah Eropa pada periode berikutnya. Para pemikir seperti Rousseau, Montesquieu, Hobbes, dan lain-lain berusaha membawa gagasan humanism terhadap peserta didik, pendidikan, serta kebijakan pendidikan terhadap wilayah jajahan sebagai konsekuensi gerakan humanisme. Gagasan humanisme memberikan penjelasan bagaimana seharusnya peserta didik dilihat dan diperlakukan menyebar ke hampir seluruh negara di Eropa. Pada waktu yang bersamaan, banyak bangsa Eropa yang melakukan penjajahan di kawasan Asia dan Afrika. Dengan demikian, gagasan tentang humanisme juga mendorong perubahan kebijakan penjajah tentang bagaimana mereka memperlakukan koloni berdasarkan gagasan humanitarian. Beberapa kawasan di Asia Tenggara di kuasai bangsa Barat, Indonesia mengalami serangkaian pengalaman penjajahan setelah pertama kali dijajah oleh Portugis, kemudian Belanda, Perancis, Inggris, dan Jepang. Secara resmi, Indonesia dijajah oleh pemerintah Belanda pada tahun 1817 mengalami berbagai perubahan kebijakan. Setelah pembubaran VOC, kebijakan colonial Belanda juga dipengaruhi oleh gerakan humanisme. Dalam konteks pendidikan, pengaruh gagasan humanisme terhadap kebijakan colonial tertuang dalam kebijakan Nativisme, Konkordansi, dan Politik Etis.Cite this article: Surya, R.A., FIkriya, R. (2022). The Contribution of Western Humanism Ideas Towards Education Policy in The Dutch East Indies (1817-1942) . Paramita: Historical Studies Journal, 32(1), 107-116. http://dx.doi.org/10.15294/paramita.v32i1.30787